Julian Horton (ed.), The Cambridge Companion to the Symphony (2013) - Rushton, Julian (Journal of the Society for Musicology in Ireland, 2015)
A review of Julian Horton (ed.), The Cambridge Companion to the Symphony (Cambridge: Cambridge University Press, 2013), ISBN: 978-0-521884-98-3.